The relationship between depression and nutritional status among the elderly adults with cardiovascular diseases in Northern Iran - Narjes Salimzadeh; Fereshteh Besharati; Azar Darvishpour; Ehsan Kazemnezhad Leili (Journal of Health, Population and Nutrition)
Abstract Background Malnutrition and depression among the elderly people with cardiovascular diseases are important public health concerns. This study made an attempt to determine the relationship between these people’s depression and their nutritional status in northern Iran. Methods This analytical cross-sectional study was conducted on 190 elderly patients hospitalized with cardiovascular diseases in Dr. Heshmat Heart Hospital in Rasht (Iran) in the 2022–2023. The research instruments included demographic information questionnaire, mini-nutritional assessment questionnaire, and geriatric depression scale. Data were analyzed by SPSS-21 software and using Chi-Square tests and ordinal logistic regression. Results The participants’ mean age was 68.4 ± 6.5 and 50.5% of the participants were women.56.3% of the elderly participants suffered from malnutrition and 96.3% of them suffered from various degrees of depression. Additionally, there was a relationship between the participants’ severity of depression and their nutritional status. Significant relationships were also observed between the participants’ depression (OR = 1.28 and p < 0.001), marital status (OR = 1.52 and p = 0.006), and underlying diseases (OR = 0.814, p = 0.035) with nutritional status. Conclusion Given the significant relationship depression with nutritional status in cardiovascular patients, early diagnosis and treatment of depression in these patients is essential to prevent the effects of depression on nutritional status and disease course.